Geoarchaeology reveals development of terrace farming in the Northern Apennines during the Medieval Climate Anomaly - Filippo Brandolini; Tim C. Kinnaird; Aayush Srivastava; Stefano Costanzo; Chiara Compostella; Sam Turner (Scientific Reports)
Abstract This study employs Optically Stimulated Luminescence Profiling and Dating (OSL-PD) to address the challenge of synchronizing social changes with natural events, a significant limitation in existing studies on the resilience and vulnerability of pre-modern societies to ecological stress. By uncovering the construction dates of terrace farming systems in the northern Apennines region, the research reveals a distinct temporal framework, indicating that the establishment of agricultural terraces predominantly occurred during the 11th to 13th centuries CE. This crucial time frame aligns directly with complex socio-economic factors, including the encastellation process, alongside the climatic shifts characterising the Medieval Climate Anomaly. Isotopic fractionation of the Total Organic Carbon confirms that different agricultural choices were made in coincidence with the establishment of terrace farming. The resultant historical rural landscape underwent continuous enhancements in the centuries that followed. Notably, the main phases of (re)construction correspond to the coldest periods of the Little Ice Age, offering new insights into the historical interactions between human activities and the environment during the Late Holocene in the area.